Geomorphology of the Sub-Antarctic Australian Territory of Heard Island-MacDonald Island - Kiernan, K; McConnell, A (1999)
The geomorphology of Heard Island-McDonald Island is primarily the product of close interplay between volcanism, glaciation, and vigorous marine process in a stormy sub-Antarctic environment. The dominant landform is the strato-volcano Big Ben (2745 m), which is the highest mountain on Australian territory outside Antarctica. Other volcanic landforms include scoria cones, domes, open vertical volcanic conduits, lava flows and lava tubes. Volcanic activity is ongoing from the summit of Big Ben, and from Samarang Hill on McDonald Island. Early, but unproven, glacial sediments may exist within the Late Miocene-Early Pliocene Drygalski Formation, which forms a 300 m high plateau along the northern coast of Heard Island. Growth of the present glaciers, some of which reach sea level, has been a response to progressive growth of the volcanoes. A variety of erosional and depositional glacial landforms is present, including major lateral moraines and extensive hummocky moraines. Vigorous longshore drift and an abundant sediment supply have produced a large spit at the downdrift end of the island, and formed bars from reworked glacigenic sediment that now impound proglacial estuarine lagoons, some of which have grown rapidly over recent decades as tidewater glaciers have retreated. Integrated study of the volcanic, glacial and coastal sequences offers the possibility of constructing a well-dated record of climate change. Research into the geomorphology, surficial sediments, and contemporary geomorphological processes, including glaciofluvial sediment flux, is also important as an aid to environmental management on land, and to management of the adjacent marine environment.